Arabidopsis Calcium Dependent Protein Kinase 3, and Its Orthologues OsCPK1, OsCPK15, and AcCPK16, Are Involved in Biotic and Abiotic Stresses - Gardette R. Valmonte-Cortes; Colleen M. Higgins; Robin M. MacDiarmid (Plants)
Calcium-dependent protein kinases (CPKs) are plant proteins that directly bind calcium ions before phosphorylating substrates involved in biotic and abiotic stress responses, as well as development. Arabidopsis thaliana CPK3 (AtCPK3) is involved with plant signaling pathways such as stomatal movement regulation, salt stress response, apoptosis, seed germination and pathogen defense. In this study, AtCPK3 and its orthologues in relatively distant plant species such as rice (Oryza sativa, monocot) and kiwifruit (Actinidia chinensis, asterid eudicot) were analyzed in response to drought, bacteria, fungi, and virus infections. Two orthologues were studied in O. sativa, namely OsCPK1 and OsCPK15, while one orthologue—AcCPK16—was identified in A. chinensis. Reverse-transcriptase quantitative PCR (RT-qPCR) analysis revealed that OsCPK1 and AcCPK16 exhibit similar responses to stressors to AtCPK3. OsCPK15 responded differently, particularly in bacterial and fungal infections. An increase in expression was consistently observed among AtCPK3 and its orthologues in response to virus infection. Overexpression mutants in both Arabidopsis and kiwifruit showed slight tolerance to drought, while knockout mutants were slightly more susceptible or had little difference with wild-type plants. Overexpression mutants in Arabidopsis showed slight tolerance to virus infection. These findings highlight the importance of AtCPK3 and its orthologues in drought and pathogen responses and suggest such function must be conserved in its orthologues in a wide range of plants.